MAGNETIC-ORDERING IN SOME ORGANIC MOLECULAR MAGNETS - Sugano, T; Pratt, F; Kurmoo, M; Takeda, N; Ishikawa, M; Blundell, S; Pattenden, P; Valladares, R; Hayes, W; Day, P (1995)
In order to study correlation between magnetic ordering and crystal structures of organic molecular magnets, zero-field muon spin rotation (mu SR), electron spin resonance (ESR) and a.c. susceptibility of the organic neutral radicals, 3-quinolyl nitronyl nitroxide (3-QNNN) and p-pyridyl nitronyl nitroxide (p-PYNN), were investigated. The onset of magnetic ordering is indicated at 0.21 K for 3-QNNN and 0.11 K for p-PYNN in the mu SR measurements as well as the a.c. susceptibility results. The magnetic structures are discussed in terms of canted ferromagnetic spin structures on the basis of molecular arrangements in the crystals. Preferred spin directions with respect to the molecular orientations of the radicals in the crystals are discussed.